Enhancing science computational thinking skills through STEM-problem-based learning with the OLabs virtual laboratory - Rahmaningsih, Adiar; Probosari, Riezky Maya; Khasanah, Annisa Nur; Supurwoko, Supurwoko; Hudha, Muhammad Nur (Indonesian Journal of Science and Mathematics Education, 2025)
This study aims to investigate the impact of the STEM–Problem–Based Learning (PBL) model, combined with the OLabs virtual laboratory, on the computational thinking skills of eighth-grade students in science education. The research used a quasi-experimental pretest–posttest control group design with a population of all eighth-grade students at SMP Negeri 1 Sukoharjo in the 2024/2025 academic year. Cluster random sampling was applied, resulting in class VIII C as the experimental class and VIII B as the control class. Data were collected using a computational thinking skills test, and hypothesis testing was conducted through the Independent Sample T-Test at a 0.05 significance level. The results showed a significant effect of the STEM–PBL model, as indicated by a significance value of 0.001 < 0.05 and a higher score improvement in the experimental class. These findings confirm that integrating STEM–PBL with the OLabs virtual laboratory effectively improves students’ computational thinking skills. This study implies the importance of implementing STEM-based problem-solving and virtual experimentation to enhance students’ computational thinking in science learning.